Цифровий друк: технологія, обладнання, матеріали - Григор’єв, О. В.; Вовк, О. В.; Майборода, Д. А. (ТОВ «Видавництво Ліра-К», 2025)
The following main indicators of modern digital equipment were analyzed: printing technology, operating principle, printing speed; image resolution, materials on which printing is carried out.
Keywords: digital equipment; друк